Joint evolutionary spectrum and autoregressive‐based approach to modeling non‐stationary flat fading channels. Issue 4 (10th February 2012) - Wang, Qing; Wu, Dapeng; Fan, Pingyi
ABSTRACT Modeling of wireless channels, especially non‐stationary fading channels, is important for design and performance analysis of wireless communication systems. Recently, we proposed a new approach to modeling non‐stationary fading channels, based on the theory of evolutionary spectrum (ES). In this paper, we develop a time‐varying autoregressive (AR) model for a non‐stationary flat fading channel; specifically, we develop a method to determine the time‐varying coefficients of the AR channel model, given the ES of a non‐stationary process. Furthermore, with the ES theory, we develop a trace‐driven time‐varying AR channel simulator to generate a non‐stationary flat fading process. Simulation results show that the ES of the channel gain process produced by our joint ES‐and‐AR‐based channel model agrees well with the user‐specified ES, indicating the accuracy of our joint ES‐and‐AR‐based channel model. Copyright © 2012 John Wiley & Sons, Ltd.